(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: The American variety of the English language, commonly referred to as American English (AmE), is a dynamic and influential linguistic system shaped by the country’s history, geography, and cultural diversity. This article explores the development, features, and social aspects of American English. It highlights key phonological, lexical, and grammatical distinctions from British English and other world varieties. The paper also discusses the impact of immigration, media, and technology on American English. Through an in-depth analysis, it aims to present a comprehensive understanding of American English as a unique and evolving variant of the global English language.